A review exploring the facets of the value of public libraries. Issue 6 (29th July 2019) - Stenstrom, Cheryl; Cole, Natalie; Hanson, Rachel
Abstract : Purpose: The purpose of this paper is to discuss a review of the literature on the value of public libraries and propose a preliminary value framework for the public library based on the results. The review was conducted and the framework was developed as part of a larger ongoing project exploring the value of California's public libraries. Design/methodology/approach: This paper is a literature review of approximately 130 international, national and local resources from 1998 to 2018. Findings were developed through an analysis and synthesis of the works as they relate to public libraries. Findings: The themes that emerged from the exploration of studies fell into three intersecting categories: support for personal advancement; support for vulnerable populations; and support for community development. A wide variety of quantitative and qualitative methods have been employed in this area of research. Among the many ways to discuss value, the most appropriate for the user will always depend on the context for which the concept of value is being defined. Practical implications: Practitioners may find the various definitions of value useful when sharing information about public libraries with decision makers and other stakeholder audiences and when designing service models and outcomes. Originality/value: The authors believe this paper is the first to identify the emergence of a value framework for the public library based on a literature review exploring both the social and financial value of public libraries.